Adherence to 5 Diet Quality Indices and Pancreatic Cancer Risk in a Large US Prospective Cohort. Issue 9 (26th April 2022) - Julián-Serrano, Sachelly; Reedy, Jill; Robien, Kim; Stolzenberg-Solomon, Rachael
Abstract: Few prospective studies have examined associations between diet quality and pancreatic ductal adenocarcinoma (PDAC), or comprehensively compared diet quality indices. We conducted a prospective analysis of adherence to the Healthy Eating Index (HEI)-2015, alternative HEI-2010, alternate Mediterranean diet (aMed), and 2 versions of Dietary Approaches to Stop Hypertension (DASH; Fung and Mellen) and PDAC within the National Institutes of Health (NIH)-AARP Diet and Health Study (United States, 1995–2011). The dietary quality indices were calculated using responses from a 124-item food frequency questionnaire completed by 535, 824 participants (315, 780 men and 220, 044 women). We used Cox proportional hazards regression models to calculate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for each diet quality index and PDAC. During follow-up through 2011 (15.5-year median), 3, 137 incident PDAC cases were identified. Compared with those with the lowest adherence quintile, participants with the highest adherence to the HEI-2015 (HR = 0.84, 95% CI: 0.75, 0.94), aMed (HR = 0.82, 95% CI: 0.73, 0.93), DASH-Fung (HR = 0.85, 95% CI: 0.77, 0.95), and DASH-Mellen (HR = 0.86, 95% CI: 0.77, 0.96) had a statistically significant, lower PDAC risk; this was not found for the alternative HEI-2010 (HR = 0.93, 95% CI: 0.83, 1.04). This prospective observational study supports the hypothesis that greater adherence to the HEI-2015, aMed, and DASH dietary recommendations may reduce PDAC.